Crónicas periodísticas de los niños trabajadores del Centro Histórico de Quito. - Granja Torres, Carlos Daniel (2012)
The "newspaper reports of child workers Quito Historic Center" is an alternative media that seeks to return the gaze to a vulnerable group of people working children. This proposal wishes to unravel the political and social positions of some media on the issue of child labor in the historic center of Quito. Therefore we performed a rigorous analysis of journalistic genres and their importance in the media to sort the information according to their specificities. Thus we glimpse the reality behind the slogan of "fair and objective information" that many media companies say they have.